2009
DOI: 10.1021/es803259g
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticle Impact on Bacterial Growth: Effect of pH, Concentration, and Organic Matter

Abstract: Silver nanoparticles (Ag NPs) are widely used as antibacterial agents. This antibacterial property carries with it a potential environmental risk once these NPs are discharged into the environment. This study investigated the impact on Pseudomonas fluorescens over a 24 h exposure of well characterized Ag NPs at pH values of 6-9, in the presence and absence of Suwannee River humic acids (SRHA). Ag NPs were characterized by size, aggregation, morphology, dissolution, and surface properties under all conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
488
2
8

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 690 publications
(543 citation statements)
references
References 27 publications
(49 reference statements)
30
488
2
8
Order By: Relevance
“…Jiang et al [36] found that the hydrodynamic diameter of TiO 2 NP aggregates varied with the solution pH, being greatest at the isoelectric point (pH 6.0). Fabrega et al [46] reported that Ag NPs stabilized by citrate coating showed no variation in aggregate size over the pH range 6 to 9, consistent with the findings of El Badawy et al [47] for similarly stabilized Ag NPs. Here, the invariant aggregate size may be explained by the relatively small variation in zeta potential of the particles in this pH range [47].…”
Section: Surface Coatingsupporting
confidence: 72%
See 1 more Smart Citation
“…Jiang et al [36] found that the hydrodynamic diameter of TiO 2 NP aggregates varied with the solution pH, being greatest at the isoelectric point (pH 6.0). Fabrega et al [46] reported that Ag NPs stabilized by citrate coating showed no variation in aggregate size over the pH range 6 to 9, consistent with the findings of El Badawy et al [47] for similarly stabilized Ag NPs. Here, the invariant aggregate size may be explained by the relatively small variation in zeta potential of the particles in this pH range [47].…”
Section: Surface Coatingsupporting
confidence: 72%
“…Here, the invariant aggregate size may be explained by the relatively small variation in zeta potential of the particles in this pH range [47]. Small aggregates of Ag NPs adsorbed humic acid, and this adsorption resulted in disaggregation (or disagglomeration) of the NPs [46].…”
Section: Surface Coatingmentioning
confidence: 94%
“…Electron microscopy is presently the predominant technique to investigate the presence, aggregation state, location, and composition of ENPs in ecotoxicological tests and on/in organisms [68][69][70] (see case study II and also Dudkiewicz et al [71], which gives a comprehensive overview of EM techniques for ENP analysis in food matrices). Both the high-resolution TEM and the field emission gun-equipped SEM or scanning transmission electron microscopy systems provide the necessary spatial resolution to visualize particles down to a few nanometers in diameter.…”
Section: Sem/tem-eds Identificationmentioning
confidence: 99%
“…For example, dissolved organic matter can be critical in controlling metal bioavailability to aquatic organisms [27]. Conversely, humic and fulvic acids are also known to reduce the toxicity of ENMs [28,29] and slow the dissolution of metal-based ENMs [30]. Moreover, natural dispersants are usually not well characterized, and the properties of natural organic matter often used in ENM experiments, such as Suwannee River humic acid, may not be representative of the wide range of organic matter in different environments.…”
Section: Dispersing Agents and Solvent Controlsmentioning
confidence: 99%
“…For example, for a 14-or 21-d plant growth test, very unstable NPs may completely dissolve during the test. This may be the case for AgNPs in liquid media [29], but it may not be a realistic representation of the fate of AgNPs in soil. For example, Shoults-Wilson et al [82] demonstrated little or no oxidative dissolution of AgNPs during a 56-d earthworm reproduction assay.…”
Section: Aging and Modifying Enms During Soil Testsmentioning
confidence: 99%